Lower limb interosseous membrane in fetuses - Katarzyna Siwek; Arthur Saniotis; Małgorzata Suchanecka; Robert Krupa; Jagoda Urbańska; Alicja Proniewicz; Paweł Dąbrowski; Maciej Henneberg; Janusz Moryś; Sławomir Kozieł (Folia Morphologica)
BACKGROUND: The leg interosseous membrane (LIM) stabilizes the tibia and the fibula. These 2 bones articulate at the proximal and distal tibiofibular joints. In addition, the LIM is the place of attachment of the tibialis anterior muscle, extensor digitorum longus muscle, fibularis tertius muscle (anatomical variant), tibialis posterior muscle, and flexor hallucis longus muscle. The specific structure of the collagen fiber network of the LIM provides durability comprising collagenous fibers that are predominately projected longitudinally, obliquely, and often transversely. MATERIALS AND METHODS: 222 human fetuses (male: 120, female: 102) between 117 and 197 (median 177) days of fetal life were available for the study. The material derived from the fetal collection is stored in the Department of Human Morphology and Embryology, Division of Anatomy of the Medical University of Wroclaw. In this study, we assessed the variability of the fetal LIM using a novel dyeing technique to identify the LIM syndesmotic structure. RESULTS: Overall, the study of the three types of interosseous fibers (transverse, oblique, longitudinal) of the right/left leg revealed that the fibers run in all three directions with frequencies approximating 60–70%. However, there were differences in the frequency of fiber directions and in the size of LIM between sexes. CONCLUSIONS: After consideration of the directions and size of fibers of LIM, parts of it can be used for reconstruction of the upper limb interosseous membrane. Sexually dimorphic features of the LIM in the studied material confirm the different dynamics of lower limb growth in each sex.